PEMERATAAN KUALITAS HASIL BELAJAR - Nurdin, Mardiana (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2010)
This article deals two main points, the interpretation and mission of education, and the equality of educational quality as the main agenda of education in the contemporary discourse. This article is expository and argumentative in nature aiming at describing the real issue. Hence, an accurate investigation is needed to get conclusive findings.